Replicating Malaysian Model of Building World-Class Universities Across Yemen - Al-haimi, Basheer; Daing Nasir, Ibrahim; Ab Hamid, Mohd Rashid (McGraw Hill Education (India) Private Limited, 2019)
Many countries have taken great interest in creating and building World-Class Universities (WCUs). Naturally, developing countries such as Yemen should also focus on establishing their own WCUs. This chapter aims to discuss two elements. First, to identify and examine past and current strategies, as well as framework reforms, that relate to building WCUs in Malaysia, and second, to propose policy recommendations to higher educational institutions, governments, policymakers and all other stakeholders for Yemen with the aim of building WCUs and enhancing the higher education system as a whole. The data gathering process performed for this chapter included reviewing official publications of studies conducted at national and international scales, as well as the existing strategies used by other countries with a similar environment to Yemen. This chapter also surveys research papers, books, and strategic planning documents for Malaysian higher education.